Implementation of Template Matching Method for Door Lock Security System Using Raspberry Pi - Beni Widiawan; Syamsiar Kautsar; Fendik Purnomo; Bety Etikasari (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
In several locations, the security system is becoming a priority. One of the location is the laboratory. There are many valuable research tools and equipment in the laboratory, so to improve the security system. Generally, the access to entry the laboratory is equipped with a digital safety system. Computer Control System Laboratory at Information Technology Department of Jember State Polytechnic uses RFID-Card as access right for entrance to the laboratory. RFID-Card also functions as ID-Card (printed with photo and biodata) and packaged to fit in user clothes pocket. However, using RFID gives less of flexibility. The user must remove the ID-Card and attach the card to the RFID reader box. Therefore, in this study will design a door lock security system based on the image processing to replace the use of RFID. Later, the user simply positions themselves in the Pi Camera work area. Processed data from the camera, the matched with image data which stored in the database. The database contains a photo of laboratory members which listed on the employee ID-Card. Template matching method is used as image matching method which stored in Raspberry Pi database. If the image which captured by camera is matched with the image data in the database, the controller will give entry access to the user. Based on the experimental results, template matching method has a success rate of 96%.